Network Externalities and Platform Strategy: Agency, Bundles Entry, and Integration - Axel Gautier; Leonardo Madio; Shiva Shekhar (CESifo GmbH, 2025)
We consider a market in which a platform hosts third-party monopolistic complementors. Users are segmented into single-use and multi-use consumers, and services exhibit network externalities. In the agency model, the presence of multi-use consumers leads complementors to set inefficiently high prices, reducing demand and the platform's profits. Platform entry can resolve these pricing inefficiencies by targeting multi-use consumers with a bundled offering, but it then fragments the market, diminishing network benefits for consumers. We find that the platform opts to enter only when it has committed to a low commission fee, and network benefits are modest. Integration with a complementor reduces prices for consumers and enhances network benefits, thereby improving consumer welfare, but the pricing inefficiency is only partially mitigated.
Keywords: L22; L86; 330; platform; network externalities; platform strategy; hybrid business model